Factors Related toIncidence of ARI in Toddlers in the Working Area of the Kolang Health Center, Kolang District, Central Tapanuli Regency - Lonrida Hutabarat (SEAN Institute, 2024)
The incidence of ARI always ranks first as the cause of death in infants and toddlers. ARI is the cause of morbidity and mortality of infectious diseases in the world. One of the developing countries with ARI cases is Indonesia, and the number is increasing every year. In addition, ARI is also often on the list of the 10 most common diseases in hospitals and health centers. Data obtained from the Kolang Health Center shows that the incidence of ARI has increased over the last three years.In 2020, 622 cases were found, including those of all ages, from toddlers, children, adults to the elderly.This study aims to determine the factors associated with the incidence of ARI in toddlers in the working area of the Kolang Health Center, Kolang District, Central Tapanuli Regency in 2021. This study is an analytical study with a cross-sectional study design. The population of this studyall patients who visited/received treatment at the Kolang Health Center totaled 345 people, and a sample of 75 people was taken using the sampling techniquesimple random sampling.The data collection method was carried out using a questionnaire, and the data analyst usedChi Square.The results of the study showedthere is relationship between nutritional status and the incidence of ARI, there is no relationship between smoking habits and the incidence of ARI, and there is a relationship between the habit of opening windows and the incidence of ARI. The conclusion of this study is that nutritional status, the habit of opening windows are significantly related to the incidence of ARI and the habit of smoking in the house has no significant relationship with the incidence of ARI. For this reason, it is recommended that mothers pay attention to toddler nutrition, come as much as possible if there is a nutritional status counseling schedule and it is hoped that families open windows every day so that ARI in toddlers does not occur or can be prevented.